2016
DOI: 10.1016/j.bbrep.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the interaction of human albumin with an anionic porphyrin

Abstract: The manuscript describes the characterization of the interaction between meso-tetrakis(p-sulfonatophenyl)porphyrin (TSPP) and human serum albumin (HSA). TSPP is a candidate for the photosensitization of structural and functional changes in proteins while HSA provides both an excellent protein model and binding and functional characteristics that could be explored in future applications of the approach. A combination of optical spectroscopic techniques (e.g., fluorescence spectroscopy, fluorescence lifetime, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The assumption is that in the 100% HSA-metal-PPX complex all the available porphyrin is already bound to the protein, thus, addition of the apo-HSA only adds free protein that cannot form further complexes with the porphyrin ligand. Previous studies have shown that metal bound protoporphyrin binds to HSA in a 1:1 ratio [15, 16]. The concentration of all solutions was adjusted with 10 mM phosphate buffer to assure that the absorbance in the analyzed wavelength range stayed below 1.0 optical density units (OD) everywhere to assure all measurements fall within the dynamic range of the instrument.…”
Section: Methodsmentioning
confidence: 99%
“…The assumption is that in the 100% HSA-metal-PPX complex all the available porphyrin is already bound to the protein, thus, addition of the apo-HSA only adds free protein that cannot form further complexes with the porphyrin ligand. Previous studies have shown that metal bound protoporphyrin binds to HSA in a 1:1 ratio [15, 16]. The concentration of all solutions was adjusted with 10 mM phosphate buffer to assure that the absorbance in the analyzed wavelength range stayed below 1.0 optical density units (OD) everywhere to assure all measurements fall within the dynamic range of the instrument.…”
Section: Methodsmentioning
confidence: 99%
“…-18 -Metalloporphyrins are widely applied to diverse aspects, such as sensors [56,57] , water purification [58,59] , catalysis [60,61] and even biological or medical uses [62][63][64] . For the past few years, a growing number of papers have demonstrated that metallopophyrin may also be a promising choice for developing OTE materials.…”
Section: Metalloporphyrin and Its Analoguesmentioning
confidence: 99%
“…On the other hand, PS binding to albumins changes their photophysical characteristics ( 17 19 ), which can modify their efficacy in photomedical applications. Characteristics of the environment, such as pH, can affect the interaction between PSs and albumins due to changes in their charge states and/or conformations ( 20 25 ); therefore, the effect of pH should be taken into account.…”
Section: Introductionmentioning
confidence: 99%